PRENUPTIAL AGREEMENT: BETWEEN A RATIONAL NECESSITY OR A LACK OF CONFIDENCE IN MARITAL LIFE? - Arif Sugitanata; Mofawg Masuwd; Arthie Amalia Rawzalgina (Universitas Islam Negeri Mataram, 2025)
This study originates from the central research question as well as the primary objective, namely examining whether a prenuptial agreement is formulated as a rational necessity in navigating the dynamics of marriage or instead reflects a lack of confidence and trust within marital life. To address this focus, the research employs a literature review method with a qualitative approach, gathering journal articles and credible academic sources from Google Scholar, Scopus, ResearchGate, Garuda, and DOAJ. All data were analysed descriptively and analytically to map how the literature interprets the motivations behind the emergence of prenuptial agreements. The findings indicate that a prenuptial agreement cannot be categorised solely as either a necessity or an indication of distrust, but rather as a neutral legal instrument whose meaning is shaped by the couple’s context. From the perspective of necessity, this instrument becomes relevant when there are significant differences in asset ownership, economic complexity, or the need for legal certainty regulated through provisions such as the Civil Code, the Marriage Law, and Constitutional Court decisions. However, the literature also shows that its formulation may be triggered by emotional anxiety, past trauma, or fear of relationship failure, thus reflecting a limited sense of security and confidence in marital life. The scientific contribution of this study lies in its more focused explanation of the ambivalence surrounding the meaning of a prenuptial agreement, specifically whether it functions as a rational planning measure or instead mirrors internal doubt, while enriching previous studies that predominantly emphasised juridical normative, legal formal, as well as social and cultural dynamics.